Early season hormonal and biochemical changes in division I field hockey players: Is fitness protective? - Walker, A. J.; McFadden, B. A.; Sanders, D. J.; Bozzini, B. N.; Conway, S. P.; Arent, S. M. (The Journal of Strength and Conditioning Research, 2020)
The purpose was to evaluate changes in hormonal and biochemical markers as a result of the accumulated stress of the initial 4-week training block in field hockey players. Women's Division I field hockey players (N = 22; Mage = 19.7 ± 1.1 years) performed testing before the start of preseason (A1) that included body composition (%BF), vertical jump, and VO2max. Blood draws were conducted at A1 to assess creatine kinase (CK), iron (Fe), hemoglobin (HGB), hematocrit (HCT), percent saturation (%sat), total cortisol (TCORT), free cortisol (FCORT), interleukin-6 (IL-6), sex hormone-binding globulin (SHBG), prolactin (PRL), vitamin D (vitD), and thyroxine (T3). Blood draws were repeated 4 weeks later (A2). Athletes were monitored during this training block, which included 2 weeks of preseason and the first 2 weeks of the season, using heart rate monitors to determine energy expenditure (Kcal) and training load. There were significant disruptions in TCORT, FCORT, T3, CK, Fe, and SHBG (p < 0.05) from A1 to A2. VO2max accounted for 31% (p < 0.05) of the variance in TCORT and %BF accounting for an additional 20.1% (p < 0.05). VO2max accounted for 32.7% (p < 0.05) of the variance in FCORT. %BF accounted for 48.9% (p < 0.05) of the variance in T3. Kcal was positively correlated with VO2max (p < 0.05) and negatively correlated with %BF (p < 0.05). Athletes with higher VO2max and lower %BF may be capable of a higher work output and therefore more likely to experience increased physiological disruptions during intense training. The high-volume nature of preseason and differences in athlete fitness capabilities require coaches to manage players at an individual level to maintain athlete readiness.